2016
DOI: 10.1016/j.palaeo.2016.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Paleoenvironmental and biogeographic implications of terminal Pleistocene large mammals from the Ziway–Shala Basin, Main Ethiopian Rift, Ethiopia

Abstract: 2016-11-03T14:11:40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Researchers have only recently begun to understand the late Pleistocene faunas of eastern Africa, despite their critical role for interpreting the paleoenvironmental context of a time and place central to the diversification and dispersal of early modern humans (Homo sapiens) (Henn et al, 2018;Scerri et al, 2018;Tryon, 2019). The late Pleistocene large mammal communities were composed of numerous extinct taxa, some of which were dominant members of the region's faunas until the onset of the Holocene (MacInnes, 1956;Marean and Gifford-Gonzalez, 1991;Marean, 1992;Faith, 2014;Faith et al, 2015;Lesur et al, 2016;Tryon et al, 2016). This emerging perspective has been reinforced by ongoing research in the Kenyan portions of the Lake Victoria Basin since 2008, which has documented numerous extinct taxa (Rusingoryx atopocranion, Damaliscus hypsodon, Kolpochoerus, and others) in late Pleistocene sediments, including new species or those formerly thought to have disappeared from eastern Africa during the middle Pleistocene (e.g., Tryon et al, 2010Tryon et al, , 2012Tryon et al, , 2016Faith et al, 2011Faith et al, , 2014Faith et al, , 2015Jenkins et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have only recently begun to understand the late Pleistocene faunas of eastern Africa, despite their critical role for interpreting the paleoenvironmental context of a time and place central to the diversification and dispersal of early modern humans (Homo sapiens) (Henn et al, 2018;Scerri et al, 2018;Tryon, 2019). The late Pleistocene large mammal communities were composed of numerous extinct taxa, some of which were dominant members of the region's faunas until the onset of the Holocene (MacInnes, 1956;Marean and Gifford-Gonzalez, 1991;Marean, 1992;Faith, 2014;Faith et al, 2015;Lesur et al, 2016;Tryon et al, 2016). This emerging perspective has been reinforced by ongoing research in the Kenyan portions of the Lake Victoria Basin since 2008, which has documented numerous extinct taxa (Rusingoryx atopocranion, Damaliscus hypsodon, Kolpochoerus, and others) in late Pleistocene sediments, including new species or those formerly thought to have disappeared from eastern Africa during the middle Pleistocene (e.g., Tryon et al, 2010Tryon et al, , 2012Tryon et al, , 2016Faith et al, 2011Faith et al, , 2014Faith et al, , 2015Jenkins et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Rusinga Hylochoerus adds to a growing body of evidence showing that geologically recent faunas are quite different from those of the present-day (Faith 2014;Faith et al 2019Faith et al , 2020. Extant species, including the Rusinga Hylochoerus, are often found well outside their historic ranges (e.g., Rowan et al 2015;Lesur et al 2016;Faith et al 2020) -leading to the formation of non-analogue species combinations -and it is becoming increasingly clear that extinct species were numerous (Faith 2014). Considerable work remains ahead if we are to sort out the emergence of what we would recognise as 'modern' eastern African faunal communities and the impact of terminal Pleistocene climatic changes in the present configuration of African ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…However, taxonomic information from these sites was either limited or unavailable for comparison at the time of this study. North of these sites, Lesur et al (2016) also reported evidence of primarily large game hunting at lakeshore LSA sites in the Zwai-Shalla Basin of the Ethiopian Rift Valley during the AHP.…”
Section: Small Animals In Mis 2 and Mis 1 Eastern Africamentioning
confidence: 95%
“…Although zooarchaeological data from MIS 2/1 sites are rare in eastern Africa, faunal studies reveal some geographic variability-but little evidence of temporal change-in the extent to which LSA groups relied on small animals. At sites dated to ~14-13 cal ka in the semi-arid Zwai-Shala Lake Basin of south-central Ethiopia, small animals accounted for only 15.5% of all fauna by number of identifiable specimens (NISP) (Lesur et al, 2016). Rock shelter and cave site assemblages from the grasslands of Kenya and Tanzania also suggest a preference for hunting larger game, with small taxa comprising <27.2% (NISP) of all animal bones dated ~ 33.5-7.6 cal ka (Marean, 1992a(Marean, , 1992bTryon and Faith, 2016).…”
Section: Introductionmentioning
confidence: 99%